2011
DOI: 10.1111/j.1744-313x.2011.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies and ethnic distribution of ABO and Rh(D) blood groups in Mauritania: results of first nationwide study

Abstract: There is no data available on the ABO/Rh(D) frequencies in the Mauritanian population. We retrospectively analysed records of a 5-year database that contained ABO/Rh phenotype and ethnic origin of 10 116 volunteers giving blood at the national blood transfusion centre to derive the frequencies of ABO/Rh(D) groups in the Mauritanian population. The two race categories in the country and their sub-ethnic groups: the Moors (whites and black) and the black Africans (Pulhars, Soninkes and Wolof) were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 11 publications
9
29
1
1
Order By: Relevance
“…[13] Other studies in Africa show highest frequencies of group O of 48.62% and 49.10% by Ndoula et al and Hamed et al respectively. [14,15] The frequencies of blood group AB in these studies are higher than that of this study, 4.45% and 4.05% against 2.47% in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…[13] Other studies in Africa show highest frequencies of group O of 48.62% and 49.10% by Ndoula et al and Hamed et al respectively. [14,15] The frequencies of blood group AB in these studies are higher than that of this study, 4.45% and 4.05% against 2.47% in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…Garratty et al reported that the total percentage of Rh‐D‐negative individuals was 14.6% among donors in the USA, varying from 1.7% in Asians to 17.3% in White non‐Hispanics . Hamed et al retrospectively analysed records from a 5‐year database containing ABO⁄Rh phenotype and ethnic origin of 10 116 volunteers that gave blood at the national blood transfusion centre in Mauritania and found that 5.77% of the Mauritanian population was Rh‐D and varied from 3.55% in Black Africans to 6.49% in Moors.…”
Section: Discussionmentioning
confidence: 51%
“…The ABO and Rh blood group systems are crucial in clinical transfusion and transplantation medicine . Previous data regarding the distribution of blood groups has mainly been obtained from blood donors, inpatients and pregnant women . The current large population‐based cross‐sectional study involved more than 3 800 000 Chinese adults from the general population and found that the largest proportion of participants had blood group A (30.54%), followed by O (30.37%), B (29.42%) and AB (9.66%).…”
Section: Discussionmentioning
confidence: 98%
“…The frequency of B antigen (18%) found to be close to than the frequencies in the mentioned 3 regions. [9][10][11] Fy (a-, b-) phenotype frequency found to be higher than the frequencies obtained in studies from India, and Rosario. Fy (a+, b-) and Fy (a-, b+) frequencies (both 12%), and Fy (a+, b+) frequency (4%) found to be less than the frequencies in the same studies.…”
Section: Discussionmentioning
confidence: 89%